Proyecto de Factibilidad para la Creación de una Empresa de Servicios de Control de Plagas para el Maíz en la Parroquia Nambacola del Cantón Gonzanamá de la Provincia de Loja - Pinta Pinta, Félix Armando (2016)
The economy of the parish Nambacola day after day facing deep structural and social changes, which are reflected in the dynamics of labor markets, and require the creation of specialized companies in order to walk to the progress of Nambacola parish, the following research work aims to contribute in some way to control pests of corn and grains for so that farmers can get good results in their crops, thus qualified staff and will, capable, efficient, effective it able to meet the expectations of the company and therefore provide a quality service. As stated above a significant contribution to the implementation of the fumigation company is expected FUMIFAST CIA. LTDA. Nambacola parish in achieving the objectives both general and specific to have a clear idea on the demand for our services offering pest control services in the maize; in this research project as scientific methods, inductive, deductive, descriptive, mathematical-statistical and literature, as well as techniques such as direct observation and survey, which is the collection of data or knowledge is used recreation. To know if this project is feasible or not, a market study was conducted by applying 305 surveys Nambacola farmers in the parish, the information that served to know the potential demand 92%; Real demand is 95%; 94% effective demand, and the supply is zero, and the unsatisfied demand is 4688.70 Nambacola farmers in the parish (for the first year of life) that should provide the service of fumigation. 5 Following a technical study focused on the place where you will find the company and will be located on the streets June 24 and Dr. Drausin Simancas corner on the size of the project you have to see the installed capacity was made the 4 hectare company fumigated daily by bomb, which a week working from Monday to Friday gives 20 services. two flowcharts were also developed describing what the process for service assistance. With regard to the legal framework organizational study was conducted, company name Company Limited, number of members 3 further structural, functional organization and manual functions for better administrative management in the company was established. Also a financial study and financial evaluation was made in order to determine the costs of the initial investment amount totaling $ 13,124.95 which members contribute each with 4374.98 Finally conclusions and recommendations are raised based on the objectives of the project.